Challenging the Ongoing Injustice of Imprisonment for Public Protection: James, Wells and Lee v The United Kingdom. Issue 6 (1st November 2013) - Bettinson, Vanessa; Dingwall, Gavin
Abstract : The Government has recently abolished Imprisonment for Public Protection, a highly controversial form of indeterminate sentence. Yet, at the time of writing, nearly 6, 000 inmates are still serving such sentences, all of whom will have to convince a Parole Board that detention is no longer necessary for the protection of the public. This paper evaluates recent European Court of Human Rights jurisprudence which considered the legality of post‐tariff detention in the absence of suitable rehabilitative provision. The Court held that there would be a violation of Article 5(1) if prisoners were held without access to such provision. Consideration is given to the implications of this ruling for those serving such sentences and, more broadly, to the impact it may have on risk‐based sentencing policies.